1984
DOI: 10.1073/pnas.81.2.371
|View full text |Cite
|
Sign up to set email alerts
|

Purification of bovine bone morphogenetic protein by hydroxyapatite chromatography.

Abstract: Bovine bone morphogenetic protein (bBMP) induces differentiation of mesenchymal-type cells into cartilage and bone. bBMP has an apparent Mr of 18,500 ± 500 and represents <0.001% of the wet weight of bone tissue. A Mr 34,000 protein resembling osteonectin is separated by extraction with Triton X-100. A Mr 24,000 protein and about half of a Mr 22,000 protein are disassociated from bBMP by precipitation in 1.5 M guanidine hydrochloride. Aggregates of bBMP and a Mr 14,000 protein are insoluble in aqueous media; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
168
1
7

Year Published

1996
1996
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 370 publications
(185 citation statements)
references
References 12 publications
9
168
1
7
Order By: Relevance
“…This is consistent with earlier studies that showed BMP-2 to be tightly associated with MGP during protein purification (7,8) and to bind to membrane-fixed MGP in ligand-blotting experiments (9). It is not clear from our experiments whether BMP-2 can still exert an effect when bound to MGP.…”
Section: The Effect Of a Large Excess Of Mgp On Osteoinduction Bysupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with earlier studies that showed BMP-2 to be tightly associated with MGP during protein purification (7,8) and to bind to membrane-fixed MGP in ligand-blotting experiments (9). It is not clear from our experiments whether BMP-2 can still exert an effect when bound to MGP.…”
Section: The Effect Of a Large Excess Of Mgp On Osteoinduction Bysupporting
confidence: 93%
“…BMP-2 belongs to the TGF-␤ superfamily of growth factors, and it is a potent inducer of bone and cartilage (6). When initially purified from bone, it was observed to be strongly associated with MGP, and strong denaturants were required to separate the two proteins (7,8). More recently, Wallin et al (9), have shown binding between MGP and BMP-2 using ligand blotting.…”
Section: Mgpmentioning
confidence: 99%
“…The BMPs (BMP1-12) are low-molecular-weight noncollagenous glycoproteins that belong to an expanding TGF-B super family of growth and differentiation factors [42][43][44][45][46]. The BMPs have a myriad of functions ranging from embryonic organogenesis to bone regeneration [47].…”
Section: Osteoinductive Growth Factorsmentioning
confidence: 99%
“…Subsequent work by Urist [50] and others [37,39,54] has identified up to 20 variants of this protein called ''bone morphogenetic protein'' (BMP), a member of the transforming growth factor b superfamily [36]. At present, only BMP-2 and BMP-7 are produced commercially as a therapy to enhance bone healing with BMP-7 called osteogenic protein 1 (OP-1).…”
Section: Introductionmentioning
confidence: 99%